NATIVE AMERICAN ORAL TRADITION IN SHERMAN ALEXIE’S RESERVATION BLUES - Anbar Mufida Az-zahra; Saprudin Saprudin; Erik Candra Pertala (Universitas Suryakancana, 2026)
The oral tradition of Native Americans is vital in maintaining their cultural identity, particularly in the face of the challenges posed by modernization and the long-standing impacts of colonialism that have threatened the existence of their original culture. Sherman Alexie’s novel Reservation Blues illustrates these elements of oral tradition and their functions within Native American culture. This research employs a phenomenological approach and Ruth Finnegan’s oral tradition theory to analyze how the elements of oral tradition in the novel serve as tools for critique and the restoration of Spokane’s cultural identity. Oral tradition is a cultural heritage from the past that needs to be preserved because, if it is not maintained and passed down to younger generations, it will simply disappear. Oral tradition serves as a means to recognize and understand the collective trauma experienced by the community at that time and to rebuild the identity of Native American society. This research concludes that the elements of oral tradition in the novel function to preserve cultural identity, reflect collective trauma, and critique the marginalization of the Spokane community. The narratives of oral tradition are also connected to Native American cultural values, revealing their struggles and resilience in the face of modernization and colonialism.